Unlocking Financial Reliability: AIS Contributions to Financial Statement Quality in Indonesian Retail Context - Michael; Widjaja, William (Politeknik Negeri Madiun, 2024)
This study examines the impact of Accounting Information Systems (AIS) on financial reporting quality in Indonesian retail firms while examining the moderating influence of internal control and user capability. Data from 110 employees in the accounting and finance departments of MSME-scale retail companies in Jakarta were analyzed using SEM-PLS. The findings underscore the significant role of AIS in enhancing financial reporting accuracy, timeliness, and completeness, thereby ensuring reliability and regulatory compliance. Moreover, internal control mechanisms were found to moderate AIS effects, safeguarding assets and enhancing operational efficiency within retail firms. Additionally, user capability emerged as a crucial moderator, influencing data interpretation and reporting timeliness. The study emphasizes the pivotal contribution of AIS to improving financial reporting quality in Indonesian retail contexts. Theoretical implications validate AIS's significance in financial reporting, while practical implications stress the importance of effective AIS implementation for retail firms. Future research avenues could explore additional factors impacting reporting quality and conduct cross-sector studies on AIS effects for a comprehensive understanding.